Fast simulation of animal locomotion: lamprey swimming - Beauregard, Matthew (2006)
Biologically realistic computer simulation of vertebrate locomotion is an interesting and challenging problem with applications in computer graphics and robotics. One current approach simulates a relatively simple vertebrate, the lamprey, using recurrent neural networks for the spine and a physical model for the body. The model is realized as a system of differential equations. The drawback with this approach is the slow speed of simulation. This paper describes two approaches to speeding up simulation of lamprey locomotion without sacrificing too much biological realism: (i) use of superior numerical integration algorithms and (ii) simplifications to the neural architecture of the lamprey.